2016
DOI: 10.1002/pen.24379
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hybrid filler networks of carbon nanotubes and carbon black on fracture resistance of styrene‐butadiene rubber composites

Abstract: In this study, influences of hybrid filler networks of carbon nanotubes (CNTs) and carbon black (CB) on fracture resistance of styrene‐butadiene rubber (SBR) composites were well investigated. The spherical CB was partially substituted by fibrous CNTs in two different ways: unequal replacement (1 phr CNTs replacing 4 phr CB) and equal replacement (1 phr CNTs replacing 1 phr CB). The J‐integral tests were employed to evaluate the crack initiation and propagation resistance. The strain amplification and distribu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Structural, mechanical, and viscoelastic properties of materials are of great importance for diverse applications and therefore a thorough characterization of these properties including stiffness and viscoelastic properties are routinely studied using dynamic mechanical analysis (DMA) technique [6]. Extensive research reports are available in the field of nanofiller reinforced polymer composites [14][15][16][17]. Reports of Lai et al [15] on the thermo-mechanical properties of nanosilica reinforced poly (ether ether ketone) (PEEK) matrix at elevated temperature from 100 C to 250 C, the effect of compactabilizers like maleic anhydride grafted polypropylene (MA-PP) and maleic anhydride grafted ethylene-propylene-diene copolymer (MA-EPDM) on wood-flour/polypropylene (WF/PP) composites by Chui-gen et al [18] are some of them.…”
Section: Introductionmentioning
confidence: 99%
“…Structural, mechanical, and viscoelastic properties of materials are of great importance for diverse applications and therefore a thorough characterization of these properties including stiffness and viscoelastic properties are routinely studied using dynamic mechanical analysis (DMA) technique [6]. Extensive research reports are available in the field of nanofiller reinforced polymer composites [14][15][16][17]. Reports of Lai et al [15] on the thermo-mechanical properties of nanosilica reinforced poly (ether ether ketone) (PEEK) matrix at elevated temperature from 100 C to 250 C, the effect of compactabilizers like maleic anhydride grafted polypropylene (MA-PP) and maleic anhydride grafted ethylene-propylene-diene copolymer (MA-EPDM) on wood-flour/polypropylene (WF/PP) composites by Chui-gen et al [18] are some of them.…”
Section: Introductionmentioning
confidence: 99%
“…This effectively improves the electrical conductivity and stress transfer in hybrid mix combinations of CB, GF and M-CNTs compared to CB filled mixes alone. 13,34 It was observed that the M-FCNTs in the compound were homogeneously distributed at low filler ratios. Increasing the amount of filler makes it difficult to prepare the mixture in a controlled manner due to multi-walled carbon nanotubes' structure.…”
Section: Resultsmentioning
confidence: 99%
“…3,12 Conductive fillers of various structures and properties are used to produce composites, where carbon-based nanomaterial is of great importance. 12,13 The superior electrical, thermal, dielectric properties and very high mechanical strength of CNTs make them ideal candidates for use in nanocomposites. 14,15 Among the carbon nanotubes, especially multi-walled carbon naıotubes (M-CNTs) are used in rubber (NR) nanocomposites production as they provide a good distribution in non-polar environments.…”
Section: Introductionmentioning
confidence: 99%
“…They attributed that to the compilation between strain-induced crystallization and cavitation at the crack tip. Dong et al [7] investigated the effects of carbon nanotubes (CNTs) and carbon black hybrid fillers on the fracture resistance of Styrene-Butadiene Rubber (SBR) composites. They used J-integral tests to evaluate crack initiation and propagation resistance.…”
Section: Introductionmentioning
confidence: 99%